PENGARUH PENDEKATAN TEACHING AT THE RIGHT LEVEL TERHADAP HASIL BELAJAR MATERI AKULTURASI BUDAYA LOKAL KELAS V SD NEGERI 200 PALEMBANG - Mustika, Putri; Sukardi; Rochayati , Rully (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by students’ low academic achievement. The study aimed to determine the effect of the TaRL approach on students’ academic achievement in the subject of Social Studies (IPAS) regarding local cultural acculturation in Grade 5 at State Elementary School 200 in Palembang. A quantitative research method was used, with Grade 5A and 5B students as the research subjects. The results showed that the average pretest scores of the control class and the experimental class indicated relatively similar initial abilities. After the treatment, the average posttest score for the control class was 79.1 and for the experimental class was 84.2. The results of the independent t-test (hypothesis) yielded an Asymp. Sig. (2-tailed) value of 0.034 < 0.05, so H₀ was rejected and Hₐ was accepted. The Teaching at the Right Level (TaRL) approach has a significant effect on learning outcomes in the IPAS subject regarding local cultural acculturation in Grade 5 at SD Negeri 200 Palembang.